Mentalization and Parental Stress: How Do They Predict Mother-Child Interactions? - María-Pía Santelices; Pamela A. Cortés (MDPI AG, 2022)
Parent-child interactions can be negatively influenced by contextual, individual, and familial factors. The present study examines how parental stress and parental mentalization predicts interactions between 36-48-month-old preschoolers and their mothers. The sample comprises 106 mother-child dyads from Santiago, Chile, from a mid-low SES. The instruments used were the Parental Stress Index-Short Form (PSI-SF), Mentalization in the Significant Adult during Interaction with the Child between 10 to 48 months old, and Parenting Interactions with Children: Checklist of Observations Linked to Outcomes (PICCOLO). A regression model was used to determine the significant impacts of mentalization and parental stress on interactions. The results indicate that the Encouragement dimension of parent-child interaction is predicted by emotional mentalization and parental distress, while the Teaching dimension of parent-child interaction is impacted by the cognitive dimension of mentalization and the perception that the child is difficult (stress difficult child). No association for the Responsivity and Affectivity dimension was observed.